Antibiotic Sensitivity of Kanagawa-positive and Kanagawa-negative Strains of Vibrio parahaernolytzcus isolated from Fishes Marketed in Kochi* - S., Sanjeev; Stephen, Jose (Fishery Technology, 2025)
Eightyfour strains of Vibrio parahaemolyticus consisting of 48 kanagawa-positive and 36 kanagawa-negative strains isolated from finfishes and shellfishes marketed in Kochi were tested for their sensitivity towards eleven antibiotics. Maximum sensitivity was observed towards chloramphenicol (98.81 %) and gentamycin (97.62%)followed by polymyxin- B(52.38%), neomycin (46.43%),tetracycline (23.81%), sulphadiazine (21.43%), ampicillin (17.86%), kanamycin (11.9%), streptomycin (11.9%) and erythromycin (1.19%). None of the isolates were found sensitive to penicillin. Among kanagawa-positive strains of V. parahaemolyticus 100% sensitivity were found towards none of the tested anttibiotics, but maximum sensitivity was shown towards chloramphenicol (97.92%) and gentamycin (95.83%).All the kanagawa-negative strains of V.parahaemolyticus was found sensitive towards chloramphenicol and gentamycin. Kanagawa-negative strains of V.parahaemolyticus were found to be more sensitive to the tested antibiotics compared to kanagawa- positive strains.